Verdict assessing the civil jury system - Litan, Robert E., 1950-; Brookings Institution; American Bar Association. Section of Litigation (Washington, D.C. : Brookings Institution, 1993)
The right to a jury trial is a fundamental feature of the American justice system. In recent years, however, aspects of the civil jury system have increasingly come under attack. Many question the ability of lay jurors to decide complex scientific and technical questions that often arise in civil suits. Others debate the high and rising costs of litigation, the staggering delay in resolving disputes, and the quality of justice. Federal and state courts, crowded with growing numbers of criminal cases, complain about handling difficult civil matters. As a result, the jury trial is effectively be.
11. Recent Innovations in Civil Jury Trial Procedures -- 12. The Modern American Jury: Reflections on Veneration and Distrust -- 13. Restructuring the Traditional Civil Jury: The Effects of Changes in Composition and Procedures -- 14. Jury Service and Community Representation -- 15. Finding the Factfinders -- Contributors -- Index -- A -- B -- C -- D -- E -- F -- G -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z
"The chapters in this volume were originally prepared for a joint project and symposium that Brookings conducted with the American Bar Association's Litigation Section in June 1992"--P. vii.
Includes bibliographical references and index.
JSTOR
Keywords: Jury -- United States; LAW / General; Jury; United States